Hybrid Revascularizaton vs Conventional CABG in Triple Vessel Disease: Mini Systematic Review - M M Afif; Nabil Dhiya Ulhak; Reyhan Bayu Kenji Harahap; Ni Putu Anindya Divy (The Indonesian Journal of General Medicine, 2025)
Background: Hybrid coronary revascularisation (HCR) integrates minimally invasive coronary artery bypass grafting (CABG) with percutaneous coronary intervention (PCI), presenting a viable alternative for managing severe triple-vessel disease (TVD). Although conventional CABG is the benchmark for multivessel disease, HCR has arisen as a method intended to diminish surgical morbidity while preserving long-term revascularisation advantages. This systematic study assesses the long-term clinical results of HCR in comparison to CABG. Methods: A computerised literature search was conducted across three search engines (Google Scholar, PUBMED, Crossref) for the years 2014-2025, with the keywords: CABG, Hybrid, TVD, and Triple Vessel. Quality of studies assessed using the Mixed Methods Appraisal Tool (MMAT) version 2018. Results: Initially, 1339 papers were retrieved; utilizing the PRISM algorithm, 2 articles were ultimately reviewed. Basman et al. (2020) discovered that the 8-year survival rates were comparable between HCR (5.0%) and CABG (4.0%), with no significant disparity in Major Adverse Cardiovascular Events (MACE) rates. Esteves et al. (2020) observed a greater incidence of adverse events in HCR (19.3%) compared to CABG (5.9%) at two years, primarily due to increased unexpected revascularisation; however, HCR demonstrated feasibility with acceptable safety. Both studies indicated that HCR is most appropriate for specific patients in whom PCI can successfully enhance minimally invasive bypass methods. Conclusions: HCR has benefits like reduced hospital durations and diminished surgical morbidity; however its long-term results do not surpass those of CABG. Increased revascularisation rates in HCR prompt apprehensions over its longevity in comparison to normal CABG. Future extensive randomised trials are necessary to formulate definitive clinical recommendations for patient selection.